An open-label, prospective study comparing efficacy, tolerability and cost of therapy of losartan with enalapril in stage 1 and stage 2 hypertension - Bindra, Rubdeep Singh; Mishra, Rajeev; Vijayendranath, Archana; Date, Sanjay K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertension is a chronic disease which insidiously affects multiple systems in the body especially the cardiovascular and cerebrovascular systems. Also being a chronic disease the patient is required to take medications lifelong and this has financial implications. This study was attempted to evaluate drugs in two antihypertensive groups: Angiotensin II antagonist losartan v/s angiotensin converting enzyme inhibitor enalapril. Methods: A total of 100 patients as per the selection criteria were enrolled in the study and allocated randomly to either group A (losartan group) or group B (enalapril group). The study period was for 12 weeks, during which regular assessments were done - first on recruitment and then at 2nd week, 4th week, 8th week, and 12th week. The assessment parameters were diastolic, systolic pressures and pulse rate. Routine investigations were performed during the 1st visit and after 12 weeks of the study period. Results: There were no significant differences between the treatment groups with respect to baseline patient demographic data and clinical characteristics like systolic blood pressure, diastolic blood pressure and heart rate. The cost benefit ratio and less adverse effects (cough), can be appreciated in group A (losartan group). Conclusions: Losartan and enalapril were well tolerated after 12 weeks of treatment with notable tolerability advantages of losartan especially with respect to the respiratory system (cough). The cost of therapy for losartan group was almost half the cost of therapy for enalapril group and hence being cost effective. Thus, losartan could be preferred as a suitable alternative to enalapril as an antihypertensive agent.